Numerical investigation of a rotating detonation engine under premixed/non-premixed conditions - Sun, Jian; Zhou, Jin; Liu, Shijie; Lin, Zhiyong (Acta astronautica, 2018)
Rotating detonation engines are widely studied because of their compact configurations and high thermal cycle efficiency. For briefty, most of the numerical simulations of rotating detonation engines used premixed reactant mixtures. The rotating detonation waves under non-premixed condition are not studied enough. Here, a series of three-dimensional numerical simulations of a rotating detonation engine under both premixed and non-premixed conditions using H2/air mixture are performed. The explicit formulation of density-based solver in ANSYS Fluent is used to perform the simulations. Two total mass flow rates of 272.3 g/s and 500 g/s are selected. When the total mass flow rate is 272.3 g/s, the engine operates at single-wave mode under both premixed and non-premixed conditions. When the total mass flow rate is 500 g/s, the engine operates at single-wave mode under premixed condition. While under non-premixed condition, a spontaneous formation of dual-wave mode is observed. This case agrees well with the phenomenon observed in experiments that as the total mass flow rate increases, the number of rotating detonation waves tends to increase. Pressure waves caused by the high pressure behind the detonation waves can propagate upstream to the H2 and air plenums. The pressure feedback in the H2 plenum is much more obvious than that in the air plenum. Due to the imperfect mixing of H2/air and the more deflagration combustion caused by the hot detonation products, the thrust of the RDE under non-premixed condition is smaller than that under premixed condition. •The flowfield in an RDE under premixed/non-premixed conditions is obtained.•In non-premixed cases, the detonation combustion occurs near the outer wall.•There are pressure disturbances in the H2 and air supplying plenums.•A spontaneous formation of dual-wave mode is observed for the non-premixed case.•The thrust under non-premixed condition has more fluctuations.